Novel founder mutation in French‐Canadian families with Naxos disease. Issue 4 (22nd February 2017) - Marino, T. Cruz; Maranda, B.; Leblanc, J.; Pratte, A.; Barabas, M.; Dupéré, A.; Lévesque, S.
Abstract :